How taxonomic change influences forecasts of the Linnean shortfall (and what we can do about it)? - Thainá Lessa; Juliana Stropp; Joaquín Hortal; Richard J. Ladle (Journal of Biogeography, 2024)
The gap between the number of described species and the number of species that actually exist is known as the Linnean shortfall and is of fundamental importance for biogeography and conservation. Unsurprisingly, there have been many attempts to quantify its extent for different taxa and regions. In this Perspective , we argue that such forecasts remain highly problematic because the extent of the shortfall does depend not only on the rates of exploration (sampling undescribed taxa) on which estimates have been commonly based but also on the rates of taxonomic change (lumping and splitting). These changes highly depend on the species concepts adopted and the information and methods used to delimit species. Commonly used methods of estimating the number of unknown species (e.g. discovery curves, taxon ratios) can underestimate or overestimate the Linnean shortfall if they do not effectively account for trends and rates of taxonomic change. A further complication is that the history of taxonomic change is not well documented for most taxa and is not typically available in biodiversity databases. Moreover, wide geographic and taxonomic variation in the adoption of species concepts and delimitation methods mean that comparison of estimates of the Linnean shortfall between taxa and even for the same taxon between regions may be unreliable. Given the high likelihood of future taxonomic changes for most major taxa, we propose two main strategies to consider the influence of taxonomic change on estimates of unknown species: (i) a highly conservative approach to estimating the Linnean shortfall, restricting analysis to groups and regions where taxonomies are relatively stable and (ii) explicitly incorporating metrics of taxonomic change into biodiversity models and estimates. In short, relevant estimates of the number of known and unknown species will only be achieved by accounting for the dynamic nature of the taxonomic process itself.